A Review on the Control of Second Order Underactuated Mechanical Systems. (2nd December 2018) - Krafes, Soukaina; Chalh, Zakaria; Saka, Abdelmjid
Abstract : This paper describes some important classes of two degrees of freedom of underactuated mechanical system and also surveys review of the recent state-of-the-art concerning the mathematical modeling of these systems, their classification, and all the control strategies (linear, nonlinear, and intelligent) that have been made so far (i.e., from the year 2000 to date) to control these systems. Future research and challenges concerning the improvement, the effectiveness, and robustness of the proposed controllers for underactuated mechanical systems are presented.